The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/4717094
|View full text |Cite
|
Sign up to set email alerts
|

Fresh-Keeping Effort and Channel Performance in a Fresh Product Supply Chain with Loss-Averse Consumers’ Returns

Abstract: We consider a fresh product supply chain consisting of one fresh product supplier and one e-tailer. Supplier sells fresh products through e-tailer in an online market, and the e-tailer offers a full-refund return policy to loss-averse consumers and exerts a freshkeeping effort to keep the product at the optimum freshness level. By developing an analytical model, we derive the optimal price, quantity, and fresh-keeping effort jointly and verify that it is unique in the centralized setting. Based on the comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 56 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Many studies make the decision of the freshness-keeping effort/preservation technology investment whose purpose is to maintain quality and reduce the volume loss rate during the transport of fresh products [2,4,6,9,10,36] or only reduce volume loss rate during storage [32,33,35], so the revenue and cost sharing contract or revenue sharing and cooperative investment contract is designed to coordinate the two-echelon [6,9,32,33,35,36] or three-echelon [10] supply chain in order to cut down on the influence of the double marginalization effect. Gu et al [37] find that both the buyback contract and a revenue-and cost-sharing contract could coordinate the supply chain consisting of one fresh product supplier and one e-retailer. Differing from all these papers, both the volume loss during transport and the quality loss during the retail of fresh agricultural products and consumer strategic behavior are simultaneously taken into account in this paper, and a two-stage pricing decision is made.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies make the decision of the freshness-keeping effort/preservation technology investment whose purpose is to maintain quality and reduce the volume loss rate during the transport of fresh products [2,4,6,9,10,36] or only reduce volume loss rate during storage [32,33,35], so the revenue and cost sharing contract or revenue sharing and cooperative investment contract is designed to coordinate the two-echelon [6,9,32,33,35,36] or three-echelon [10] supply chain in order to cut down on the influence of the double marginalization effect. Gu et al [37] find that both the buyback contract and a revenue-and cost-sharing contract could coordinate the supply chain consisting of one fresh product supplier and one e-retailer. Differing from all these papers, both the volume loss during transport and the quality loss during the retail of fresh agricultural products and consumer strategic behavior are simultaneously taken into account in this paper, and a two-stage pricing decision is made.…”
Section: Literature Reviewmentioning
confidence: 99%
“…where μ is the degree of fairness concern and λ is the coefficient of sympathy, μ, λ ≥ 0, and 0 < λ < 1. e first part of equation (12) reflected the retailer's profit, whereas the second part evaluated the utility loss from disadvantageous inequality for the retailer when π m > π r , and the third part measured the loss from advantageous inequality for the retailer when π m < π r . Note that if the retailer's profit was worse than the manufacturers' profit (i.e., π m > π r ), the retailer will have negative utility under the condition of unfair aversion.…”
Section: Centralized Supply Chain Modelmentioning
confidence: 99%
“…Based on the process above, we took the first-order and second-order partial derivatives of optimal wholesale price w d * with respect to β and μ in equation (12), respectively:…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…In the supply chain coordination of fresh agricultural products, Gu, Fu, and Li (2018) studied a fresh product supply chain consisting of a fresh product supplier and an e-retailer, and derived the optimal price, quantity and fresh-keeping effect by analyzing the model. In the end, it is shown that the rate of return has nothing to do with the loss of freshness and the loss of consumers.…”
Section: Introductionmentioning
confidence: 99%